Bystander Ethics and Good Samaritanism: A Paradox for Learning Health Organizations. Issue 4 (20th August 2019) - Sabin, James E.; Cocoros, Noelle M.; Garcia, Crystal J.; Goldsack, Jennifer C.; Haynes, Kevin; Lin, Nancy D.; McCall, Debbe; Nair, Vinit; Pokorney, Sean D.; McMahill‐Walraven, Cheryl N.; Granger, Christopher B.; Platt, Richard
Abstract: In 2012, a U.S. Institute of Medicine report called for a different approach to health care: "Left unchanged, health care will continue to underperform; cause unnecessary harm; and strain national, state, and family budgets." The answer, they suggested, would be a "continuously learning" health system. Ethicists and researchers urged the creation of "learning health organizations" that would integrate knowledge from patient‐care data to continuously improve the quality of care. Our experience with an ongoing research study on atrial fibrillation—a trial known as IMPACT‐AFib—gave us some insight into one of the challenges that will have to be dealt with in creating these organizations. Although the proposed educational intervention study placed no restrictions on what providers and health plans could do, the oversight team argued that the ethical principle of beneficence did not allow the researchers to be "bystanders" in relation to a control group receiving suboptimal care. In response, the researchers designed a "workaround" that allowed the project to go forward. We believe the experience suggests that what we call "bystander ethics" will create challenges for the kinds of quality improvement research that LHOs are designed to do .